2004
DOI: 10.1158/0008-5472.can-04-0899
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hypoxia-Regulated Proteins in Head and Neck Cancer by Proteomic and Tissue Array Profiling

Abstract: Hypoxia within solid tumors decreases therapeutic efficacy, and identification of hypoxia markers may influence the choice of therapeutic modality. Here, we used a proteomic approach to identify hypoxia-regulated proteins and validated their use as endogenous indicators of tumor hypoxia. Using two-dimensional gel electrophoresis and PowerBlot (antibody-based array), we identified a group of 20 proteins that are increased >1.5-fold during hypoxia. The majority of these proteins such as IB kinase ␤ (IKK␤), MKK3b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…The presence of an HIF-␣ LxxLAP consensus motif in IKK␤ led us to examine the expression of these proteins under hypoxia. In line with previous studies (15), HeLa cells exposed to graded hypoxia for 24 h demonstrated increased IKK␤ protein levels, whereas IKK␥/ NEMO (which does not contain the hydroxylation motif) did not increase (Fig. 5A).…”
Section: Resultssupporting
confidence: 92%
“…The presence of an HIF-␣ LxxLAP consensus motif in IKK␤ led us to examine the expression of these proteins under hypoxia. In line with previous studies (15), HeLa cells exposed to graded hypoxia for 24 h demonstrated increased IKK␤ protein levels, whereas IKK␥/ NEMO (which does not contain the hydroxylation motif) did not increase (Fig. 5A).…”
Section: Resultssupporting
confidence: 92%
“…Although HIF controls the expression of many hypoxiaregulated genes, expression profiling studies conducted under hypoxia (21)(22)(23)(24)(25)(26)(27)(28) reveal that HIF activation alone cannot account for the full repertoire of changes that occur intracellularly as oxygen becomes limiting. Hypoxic cells elicit additional HIF-1-independent adaptive responses that contribute to increased survival under low oxygen conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al identified the hypoxia-regulated proteins in HNC by proteomic and tissue array profiling. 81 Hypoxia is a major determinant of local, regional, and distant failure after anticancer therapy. 82 At the molecular level, hypoxia selects tumors with an increased malignant phenotype, 83 resulting in resistance to apoptosis and greater propensity for distant metastases.…”
Section: Hnc Physiology Biomarker Studiesmentioning
confidence: 99%
“…In human HNSCC, expression of this protein appeared to be a good indicator of tumor hypoxia and may represent a novel anticancer therapeutic target. 81 Studying the normal to tumor transition of esophageal SCC, Chung et al quantified the change in 7 proteins in this tissue transition using multiplex tissue immunoblotting. 84 Their data suggest that decreased expression of pan-cytokeratin (CK)-4, CK-14, and annexin 1 are early events.…”
Section: Hnc Physiology Biomarker Studiesmentioning
confidence: 99%